The Effectiveness of Project-Based Learning On 4Cs Skills of Vocational Students in Higher Education - Syahril; Purwantono; Wulansari , Rizky Ema; Nabawi, Rahmat Azis; Safitri, Dian; Kiong , Tee Tze (Journal of Technical Education and Training, 2022)
The results of the previous study showed that the implementation of the project which is based on the potential of the students’ region was better in improving soft skills, engagement and core competencies of learning for students. This study aims to continue the investigation on revealing the effectiveness of the model in improving the students’ 4Cs skills. It is driven by educational needs in this 21st century which requires vocational students to have those skills to adapt to the complexities of the real industry. This study was conducted by using a quasi-experimental method. The potential of the students’ region-based project was implemented to an experimental group; meanwhile, the free theme-based project was administered to a control group. Upon completion of the assessment, each student's 4Cs skill in the experimental group had higher scores than those of the control group. Overall, after being analysed by using ANCOVA, there were significant differences found between the 4Cs skills scores of the experimental group and those of the control group. Therefore, it can be concluded that the project which is based on the potential of the students’ region is more effective in improving the 4Cs skills of vocational students in higher education than the free theme based-project is. The syntaxes of the project based on the potential of students’ region explained here can be a reference for teachers and lecturers in implementing it. In addition, as it is being developed, it can also inspire and be a reference for other researches focusing their study in the learning quality development at vocational education.